HER-2 overexpression is a negative predictive factor for recurrence in patients with non-muscle-invasive bladder cancer on intravesical therapy. Issue 1 (January 2020) - Moustakas, Georgios; Kampantais, Spyridon; Nikolaidou, Anastasia; Vakalopoulos, Ioannis; Tzioufa, Valentini; Dimitriadis, Georgios
Objective: HER-2 is overexpressed in a variety of human malignant tumors and has been widely used in the prognosis and treatment of breast cancer. In urothelial cell carcinoma of the bladder, some reports have shown an association between HER-2 overexpression and worse outcomes. The aim of this study was to examine the association between HER-2 expression and other clinicopathologic parameters in 48 patients treated for primary non-muscle-invasive transitional cell carcinoma of the bladder. Methods: The initial expression of HER-2 in tumor specimens and its expression upon disease recurrence following instillation therapy (BCG, Mitomycin, or Epirubicin) were studied. Results: HER-2 expression was significantly increased between these two timepoints. In multivariate analysis, HER-2 expression at the time of diagnosis was found to be the only independent factor and was associated with reduced recurrence free survival. Conclusions: HER-2 status could be an additional biomarker for predicting the outcome of non-muscle-invasive bladder cancer, which could help identify high-risk patients for recurrence and possible progression who require close observation and perhaps radical treatment, such as early cystectomy.